Authentication protocols based on low−bandwidth unspoofable channels: a comparative survey - Nguyen, L; Roscoe, A (2011)
One of the main challenges in pervasive computing is how we can establish secure communication over an untrusted high-bandwidth network without any initial knowledge or a Public Key Infrastructure. An approach studied by a number of researchers is building security though human work creating a low-bandwidth empirical (or authentication) channel where the transmitted information is authentic and cannot be faked or modified. In this paper, we give an analytical survey of authentication protocols of this type. We start with non-interactive authentication schemes, and then move on to analyse a number of strategies used to build interactive pair-wise and group protocols that minimise the human work relative to the amount of security obtained as well as optimising the computation processing. In studying these protocols, we will discover that their security is underlined by the idea of commitment before knowledge, which is refined by two protocol design principles introduced in this survey.